Penanaman Karakter Leader Berintegritas pada Organisasi Santri Ar-Rohmah - Wahid Nur Afif; Afiful Ikhwan; Happy Susanto (JIE (Journal of Islamic Education), 2023)
Instilling a leader character with integrity is an important requirement to be achieved in the educational process. The values that are embedded in the personality of the Ar-Rohmah students have a positive impact in contributing to the organization both within the orphanage and in the community. This study aims to describe the concept, implementation, and results of implementing the character of a leader with integrity in the Ar-Rohmah santri organization. This type of research is qualitative research, with a natural approach (natural setting). The subjects of this research were the leaders of the orphanage, the care department, and the head of the ISA organization (Ar-Rohmah Santri Association). Data collection techniques are carried out through interviews, observation, and documentation of data related to research. The analysis technique used is the Milles and Huberman qualitative analysis model, data reduction, data display, and verification. Checking the validity of the data uses triangulation: credibility, transferability, precedence, and confirmability. The findings of this research are that the cultivation of a leader character with integrity in the Ar-Rohmah Santri Association (ISA) organization begins with systematic and measurable concept planning by the ISA chairman. The results of the planning are then implemented based on daily, weekly, monthly and annual programs using three methods, namely communication methods, evaluation and providing sanctions to students who violate them.